Lokakarya Optimalisasi Komunitas Belajar Guru-guru Sekolah Dasar Di Kabupaten Barru - Sayidiman Sayidiman; Hardianto Rahman; Muhammad Faisal; Ahmad Syawaluddin; Afdhal Fatawuri Syamsuddin (KARYA: Journal of Educational Community Service, 2024)
The objective of the Workshop "Optimizing Elementary School Teachers' Learning Communities in Barru District" is to enhance the quality of learning, foster innovation and creativity, and increase community participation. The method used involves delivering content and practice through the Free Learning Flow method developed by the Ministry of Education and Culture. The steps in the Free Learning Flow include: starting from oneself, exploring concepts, collaborative space, contextual demonstration, elaborating understanding, connecting between materials, and taking real action.The outcomes of this activity include: enhancing the quality of learning, where the workshop successfully facilitated improvements through collaboration among learning community members. Evaluation survey data shows that 90% of participants reported an improvement in learning quality in Barru District after participating in the workshop. Analysis of teacher competency test results also indicates a significant improvement in mastering teaching methods that are more responsive to student needs. Additionally, the workshop successfully encouraged innovation and creativity, resulting in over 15 innovative ideas related to developing new teaching methods tailored to local needs. 80% of these ideas have been effectively implemented in several schools in Barru District after the workshop concluded. Lastly, the high attendance rate in the workshop, averaging 95% of the total invited participants, demonstrates the community's high level of participation. Survey data also shows that 85% of respondents expressed willingness to participate in future educational development activities, indicating an increased community participation spirit after the workshop